A sterol-like odorant in the urine of Mozambique tilapia males likely signals social dominance to females. - Barata, Eduardo N. (2008)
Many species of freshwater fish with relatively simple mating strategies release hormonally derived sex pheromones in urine. However, it is not known whether species with more complex reproductive strategies use specialized urinary chemical signals. We addressed this by using the Mozambique tilapia (Oreochromis mossambicus Peters 1852), a lek-breeding species in which males establish dominance hierarchies and visiting females mate preferentially with territorial/dominant males. We measured urination frequency of territorial males in social isolation and in the presence of females that were either ready to spawn or had finished spawning. In groups of fish, we monitored the volume of urine stored in subordinate and dominant males to determine if urine volume and olfactory potency (by recording electro-olfactograms, EOG, in females) are related to the male’s social rank. Dominant, territorial males stored more urine than subordinates and released it in short pulses, the frequency of which increased in the presence of females ready to spawn but not in the presence of post-spawn females. Urine from subordinate and dominant males was fractionated by liquid chromatography and fractions tested for olfactory potency by using the EOG, with the most potent fraction analyzed by mass spectrometry (MS). The olfactory system of females was sensitive to a urinary compound that was more abundant in the urine of dominant males than in that of subordinates. MS analysis suggested the compound is a sulfated aminosterol- like compound with a formula of C29H40N2O10S. Therefore, we suggest that dominant/territorial tilapia males dramatically increase urination frequency in the presence of females ready to spawn and that the urinary odorant acts as a pheromonal signal of dominance, thereby influencing female spawning.